THE Effect Of Project Based Learning On Ips Students' Learning Outcomes In Class V In Online Learning : Pengaruh Project Based Learning Terhadap Hasil Belajar IPS Siswa Kelas V dalam Pembelajaran Daring - Maulidati Hasanah; Ruli Astuti (Academia Open, 2021)
This study aims to determine the effect of implementing Project Based Learning (PJBL) on student social studies learning outcomes at MIN 01 Karangasem Bali. From the results of observations, researchers know that the social studies learning outcomes for class V MIN 01 Karangasem Bali are low below the KKM. This type of research is a type of quantitative research with experimental methods. The population in this study were all students of class I-VI MIN 01 Karangasem Bali, amounting to 438 students and the sample in this study amounted to 27 students. Based on the results of research on the application of Project Based Learning, it is known that there is an influence on student learning outcomes. Changes in student learning outcomes are shown by the results of the analysis of the effect of the sig value of 0.064 > 0.005 with a t table of 1.706 > 0.05 then t count < from t table which results in HO being rejected and HA being accepted.